Biographical dictionary of civil engineers in Great Britain and Ireland. Volume 3, - Chrimes, Mike (ICE Publishing, 2014)
The third volume of the authoritative source of information on the engineers who designed public works over the past 300 years. 'Biographical Dictionary of Civil Engineers in Great Britain and Ireland' discusses the lives of the people who were concerned with awe-inspiring engineering feats between the years 1891-1920 including building harbours and lighthouses, fen drainage and improving river navigations, building canals, roads, bridges and early railways, and providing water supply facilities. This book is the definitive biographical reference work on the lives, works and careers of individuals engaged in the practice of civil engineering. Richly illustrated, this book is an engaging read for any engineer and also provides great value to engineers involved in restoration work.